Thin film fabrication for optimal reflectivity coatings at 1064nm - Xiao, Zed Zhiqiang (2009)
In collaboration with Defence Science Organization, this project aim to achieve optimal reflectivity at 1064nm using Filter Cathodic Vacuum Arc (FCVA) technique. It involved fabrication of single and multi-layer thin film coating using Silicon and Titanium target. In this project, depositions are done on the Fused Silica and Yttrium aluminum garnet (YAG) to achieve highly reflective and anti-reflective respectively. Precise thickness of each layer is carefully observed to achieve the optimum result at 1064nm wavelength. The design which includes the thickness of each individual layer (using TiO2 and SiO2) is generated using the Essential Macleod program.